2013
DOI: 10.1158/1078-0432.ccr-12-0652
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib plus Capecitabine for Advanced Breast Cancer: Safety and Efficacy in Phase I Study CA180004

Abstract: Purpose: Dasatinib is an Src family kinase inhibitor with modest activity in advanced breast cancer. We aimed to assess toxicity and maximum tolerated dose (MTD) for dasatinib plus capecitabine, estimate efficacy, and explore effects on angiogenesis.Experimental Design: Dose levels (DL) were dasatinib 50 mg twice daily (DL1), 70 mg twice daily (DL2 and DL3), or 100 mg daily (DL3a); plus capecitabine on days 1 to 14 of a 21-day cycle, at 825 mg/m 2 twice daily (DL1 and DL2) or 1,000 mg/m 2 twice daily [DL3 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
2
28
1
Order By: Relevance
“…Several clinical studies have evaluated the use of selective src inhibitors like Dasatinib or Saracatinib for treating breast cancer [14, 15]. Preclinical data demonstrated saracatinib decreased cell growth and migration in MDA-MB-231 breast cancer cell line and xenograft models, however, it was later shown to be ineffective as single agent therapy in clinical trials [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have evaluated the use of selective src inhibitors like Dasatinib or Saracatinib for treating breast cancer [14, 15]. Preclinical data demonstrated saracatinib decreased cell growth and migration in MDA-MB-231 breast cancer cell line and xenograft models, however, it was later shown to be ineffective as single agent therapy in clinical trials [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…A combination of dasatinib and capecitabine or gemcitabine has been shown to have potential for the treatment of breast cancer. 21,22) Taking into account the phase 2 clinical trials of gefitinib and dasatinib against breast cancer, we speculated that there would be a synergistic effect of dasatinib or gefitinib combined with the antimetabolite drug cladribine in the treatment of breast cancer. …”
mentioning
confidence: 99%
“…82 Combination trials have shown improved outcomes in patients with breast cancer, for example Phase I clinical trials of dasatinib with Capecitabine show clinical response rates of 56% in unselected patients. 83 Other trials combining dasatinib with paclitaxel 84 and bosutinib with exemestane 85 are currently underway in patients with advanced metastatic breast cancer and are showing improved responses compared to single agents alone. These preliminary results suggest that the efficacy of SFK inhibitors will likely be improved by combining these drugs with others that increase potency or have parallel cytotoxic activity.…”
Section: Mcl-1 Regulation Of Src Family Kinase Signalling; Implicatiomentioning
confidence: 99%